'It was as if my ballet had never existed!': August Bournonville and the Reception of Brudefærden i Hardanger. (May 2021) - Sasser, Patricia Puckett
Abstract : Set in Norway, August Bournonville's 1853 ballet Brudefærden i Hardanger was highly successful with both Danish and Swedish audiences. In Norway, however, the ballet was ignored and ultimately blamed for perpetuating false images of the nation. This paper explores the ways in which Norway functioned as a source of idealism, exoticism, and romantic nationalism in nineteenth-century Scandinavia. The contrasting attitudes towards Bournonville's work illuminate more than differences of tastes among the three countries. As contemporary accounts, sheet music, prints, and performance ephemera demonstrate, Brudefærden i Hardanger reveals the ways in which Bournonville's ballet created, interpreted, and also constrained national identity.